Pemanfaatan minyak jelantah menjadi sabun batang pada masyarakat kelurahan Air Hitam Pekanbaru - Annie Mustika Putri; Yaumul Fazri; Tauhid Abdul Ghani Setyo Wibowo; Dini Maharani Putri (Universitas Hamzanwadi, 2023)
Every cooking activity in households inevitably generates waste commonly known as waste or garbage, whether in solid or liquid form. One of these wastes is used cooking oil, commonly referred to as used cooking oil or